ELFN1-AS1 accelerates cell proliferation, invasion and migration via regulating miR-497-3p/CLDN4 axis in ovarian cancer. Issue 1 (1st January 2020) - Jie, Youkun; Ye, Lu; Chen, He; Yu, Xiaohong; Cai, Li; He, Wenfeng; Fu, Yonghui
ABSTRACT: Previous studies indicated that long non-coding RNAs (LncRNAs) were involved in the progression of multiple cancers including ovarian cancer (OV). LncRNA ELFN1-AS1 functioned as an oncogene in many cancers, but its potential roles in OV were largely unclear. In the current study, we were aimed at clarifying the biological roles and molecular mechanisms of ELFN1-AS1 in OV. We found that ELFN1-AS1 was significantly upregulated in OV tissues and cell lines. High expression of ELFN1-AS1 was associated with poor prognosis in OV patients. Knockdown of ELFN1-AS1 inhibited the proliferation, migration and invasion of SKOV3 cell lines and repressed tumor growth in xenografted ovarian models. Mechanistically, ELFN1-AS1 promoted the proliferation, migration and invasion of SKOV3 cells by sponging miR-497-3p. Additionally, CLDN4 was verified to be the target of miR-497-3p. Rescue experiments revealed that miR-497-3p inhibition could partly reverse the inhibitory effect of ELFN1-AS1 silencing on proliferation, migration and invasion of SKOV3 cell lines. Taken together, our findings indicated that ELFN1-AS1 acted as an oncogene in ovarian cancer through regulating the expression of CLDN4 by directly interacting with miR-497-3p. The results suggested that ELFN1-AS1 might act as a promising therapeutic target for OV. Graphical abstract: